Acid-based titration and cation test handbook - Hamzah, Hairul Hisham; Samsudin, Mohd Ali; Yakob, Noor Aida; Kaus, Noor Haida Mohd; Ishak, Nor Asniza; Jaafar, Nur Farhana; Ahmad, Nur Jahan; Adawiyah, Rabiatul; Adnan, Rohana (Universiti Sains Malaysia, 2020)
This handbook is prepared in order to integrate the microscale approach into the chemistry curriculum of Malaysian secondary schools taking into consideration the limited funding in terms of chemicals, glassware and laboratory facilities.